Homework Help

Show the equation f (x)-2x =0 have 1 solution <2 and >1. f  co ntinue  integral...

user profile pic

kikilex | Student, Undergraduate | (Level 2) eNoter

Posted May 19, 2013 at 4:11 PM via web

dislike 1 like

Show the equation f (x)-2x =0 have 1 solution <2 and >1. f  co ntinue 

integral 1-2 f(x)dx =3

2 Answers | Add Yours

user profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted May 19, 2013 at 5:04 PM (Answer #1)

dislike 2 like

You need to consider the following function `g(x) = f(x) - 2x` , hence, integrating the function `g(x)` yields:

`int_1^2 g(x) dx = int_1^2 (f(x) - 2x) dx`

Using the proeprty of linearity of integral yields:

`int_1^2 g(x) dx = int_1^2 (f(x))dx - int_1^2 2x dx`

Since the problem provides the information that `int_1^2 (f(x))dx = 3` , yields:

`int_1^2 g(x) dx = 3 - 2 int_1^2 x dx`

`int_1^2 g(x) dx = 3 - 2 x^2/2|_1^2`

Reducing duplicate factros and using the fundamental theorem of calcululs yields:

`int_1^2 g(x) dx = 3 - (2^2 - 1^2) = 0`

Since the problem provides the information that `f(x)` is continuous over `[1,2]` , hence, g(x) is also continuous over `[1,2]` , thus, you may use the mean value theorem, such that:

`g(c) = (int_(1^2)g(x)dx)/(2-1)`

Replacing c for x in equation of `g(x) ` yields:

`f(c) - 2c = 0=> c in [1,2]` is the solution of the equation `f(x) - 2x = 0`

Hence, testing if there exists a solution to equation `f(x) - 2x = 0, x in [1,2]` , yields, using the mean value theorem, that there exists `c in [1,2],` such that `f(c) - 2c = 0` .

user profile pic

oldnick | (Level 1) Valedictorian

Posted May 20, 2013 at 2:25 AM (Answer #2)

dislike 0 like

Then we can say:

`G(x)= int( f(x)-2) dx`

`G(1)-G(2)=int_1^2 (f(x)-2x) dx` `=int_1^2 f(x) dx- int_1^2 2xdx=`

`G(x)= 3-[x^2/2]_1^2=3-(2^2-1^2)=0`

Since `f(x)`  is continue  `f(x)-2x`  is also contiue, so for Torricelli Barrow Theorem, `G(x)` , is the integral function of `f(x)-2x` , and also continue.

So:  `G(x) `  has the same value for `x=1`  and `x=2`

Then for Lagranges Theorem:  `EE xi , 1 <= xi <= 2` , so that:

`G'( xi)(2-1)= 0` `rArr`   `G'(xi)=0`  `rArr`   `f(xi)-2xi=0`

That means `xi`  is solution of `f(x)-2x=0`

 

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes